2022
DOI: 10.4103/aja.aja_33_21
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord Wharton's jelly-derived mesenchymal stem cell transplantation could improve diabetic intracavernosal pressure

Abstract: Mesenchymal stem cells (MSCs) secrete various cytokines with angiogenic and neuroprotective effects. This study aimed to assess the effects of human umbilical cord Wharton's jelly-derived MSCs (hWJ-MSCs) on diabetes-related intracavernosal pressure (ICP) impairment in rats. hWJ-MSCs were isolated from human umbilical cord Wharton's jelly and transplanted into the corpus cavernosum of streptozotocin (STZ)-induced diabetic rats by unilateral injection. The erectile function was evaluated at 4 weeks, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Shin et al found that HUC-MSC transplantation improved urinary function in DM rats, which provides a rationale for HUC-MSC treatment of DM-related detrusor underactivity (DUA) (124). Wu et al found that HUC-MSC transplantation may improve diabetic erectile dysfunction in rats by increasing the production of paracrine growth factors (VEGF), endothelial nitric oxide synthase (eNOS), IGF1, and basic fibroblast growth factor (bFGF) (125). In conclusion, transplantation of HUC-MSCs may be a new potential therapeutic option for DAN.…”
Section: Diabetic Autonomic Neuropathymentioning
confidence: 99%
“…Shin et al found that HUC-MSC transplantation improved urinary function in DM rats, which provides a rationale for HUC-MSC treatment of DM-related detrusor underactivity (DUA) (124). Wu et al found that HUC-MSC transplantation may improve diabetic erectile dysfunction in rats by increasing the production of paracrine growth factors (VEGF), endothelial nitric oxide synthase (eNOS), IGF1, and basic fibroblast growth factor (bFGF) (125). In conclusion, transplantation of HUC-MSCs may be a new potential therapeutic option for DAN.…”
Section: Diabetic Autonomic Neuropathymentioning
confidence: 99%